2023
DOI: 10.7759/cureus.34644
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High-intensity and High-impact Exercises in Improving Bone Health in Postmenopausal Women: A Systematic Review

Abstract: Postmenopausal osteoporosis is a chronic condition with decreased bone mass and altered bone structure, leading to a greater risk of fractures among older women. Exercise has been proposed as a potentially effective non-pharmacological method to prevent this condition. In this systematic review, we investigate the effects and safety of high-impact and high-intensity exercises in improving bone density at popular sites of fragility fractures, namely, the hip and spine. This review also highlights the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…High-impact loading exercises, such as one-foot jumps, positively impact the Bone Material Strength index (BMSi), [22] and they have been shown to reduce the occurrence of osteoporosis. [23] Jumping on a trampoline has also been proven to have a substantial influence on bone strength, resulting in the growth of tibial and radial bone radius and density. [20] Rebounding on a mini-trampoline resulted in blood marker changes, including decreased osteoclast activity (lower C-terminal telopeptide concentration), increased osteoblast activity (higher osteocalcin concentration), and an improved calcium-homeostasis profile (higher calcium and potassium concentrations, lower parathormone concentration).…”
Section: Cardiovascular Effect: Effect On Vo2maxmentioning
confidence: 99%
“…High-impact loading exercises, such as one-foot jumps, positively impact the Bone Material Strength index (BMSi), [22] and they have been shown to reduce the occurrence of osteoporosis. [23] Jumping on a trampoline has also been proven to have a substantial influence on bone strength, resulting in the growth of tibial and radial bone radius and density. [20] Rebounding on a mini-trampoline resulted in blood marker changes, including decreased osteoclast activity (lower C-terminal telopeptide concentration), increased osteoblast activity (higher osteocalcin concentration), and an improved calcium-homeostasis profile (higher calcium and potassium concentrations, lower parathormone concentration).…”
Section: Cardiovascular Effect: Effect On Vo2maxmentioning
confidence: 99%
“…1 Current strategies aimed to optimizing bone mass to help in reducing the risk of osteoporosis-related fractures include physical activities. 2,3 It has been reported that normal walking 4 is not associated with bone mineral density (BMD) changes in the femoral neck whereas jogging combined with walking 5 , running, and jumping [6][7][8] were the most effective in improving bone density and other parameters of bone health. Nevertheless, the optimal type and intensity of exercises that enhance bone mass are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%